Median sternotomy for an unexpected complication of permanent hemodialysis catheters: stuck catheter - ARSAN, SİNAN (VERLAG HANS HUBER, 2008)
Cuffed tunneled venous access catheters are commonly used for temporary and permanent access in patients undergoing hemodialysis. These catheters play an essential role in providing permanent access in patients in whom all other access options have been exhausted. However, they are prone to several complications like catheter thrombosis, catheter fibrin sheating and infection. Herein, we report two uncommon cases of stuck hemodialysis cuffed tunneled catheters causing stenosis and thrombosis in central veins which needed to be removed by median sternotomy.
Keywords: hemodialysis catheters; cuffed tunnelled venous access; stuck catheter; VASCULAR ACCESS